Confirmed Record of the Two-Faced Toadfi sh, Bifax Lacinia Greenfi eld, Mee & Randall, 1994 (Fam. Batrachoididae) From the Southern Oman Coast of the Arabian Sea - Chesalin Mikhail; Al-Shajibi Said (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
The presence of two-faced toadfish Bifax lacinia was confirmed based on a single specimen, 244 mm standard length (SL), caught in the waters of Salalah port, Oman, the Arabian Sea in February 2016. Descriptions, illustrations, meristic and morphometric data are presented. The species is considered as an endemic of the southern Oman waters. Currently, the habitat of B. lacinia in Salalah port is under threat of the destruction due to the planned extension of the port.